2022
DOI: 10.1002/ajoc.202200112
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Expanded Crowned Macrocycles Containing Two Pyrrolo[1,2‐a]indole Units

Abstract: Expanded crowned macrocycles containing two pyrrolo[1,2‐a]indole moieties in their macrocyclic framework have been synthesized by condensing a 1,4‐bis(2‐thienyl) benzene‐based diol with three different crown based tripyrranes under acid‐catalyzed conditions. HRMS and NMR studies were used to deduce the molecular structures of fused expanded crowned macrocycles. The studies indicated the occurrence of two intramolecular fusions between two core pyrrolic nitrogens with carbon atoms of two phenylene groups to gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Synthesis of p– benzi based pentapyrrane (6) : A sample of 1,4‐phenylenebis(thiophene‐5,2‐diyl))bis((4‐(tert‐butyl)phenyl)methanol [41] (1 g, 1.773 mmol) and pyrrole (1.2 ml, 17.730 mmol) were dissolved in 100 mL of CH 2 Cl 2 in a 250 mL of round bottom flask at room temperature and N 2 gas was purged for 10 min. To initiate the reaction, BF 3 ⋅OEt 2 (25 μl, 0.177 mmol) was added and reaction mixture was allowed to stir at room temperature for 30 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Synthesis of p– benzi based pentapyrrane (6) : A sample of 1,4‐phenylenebis(thiophene‐5,2‐diyl))bis((4‐(tert‐butyl)phenyl)methanol [41] (1 g, 1.773 mmol) and pyrrole (1.2 ml, 17.730 mmol) were dissolved in 100 mL of CH 2 Cl 2 in a 250 mL of round bottom flask at room temperature and N 2 gas was purged for 10 min. To initiate the reaction, BF 3 ⋅OEt 2 (25 μl, 0.177 mmol) was added and reaction mixture was allowed to stir at room temperature for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…The 1,4-phenylenebis(thiophene-5,2-diyl)bis((4-(tertbutyl)phenyl)methanol [41] and 1,3-bis(5-((4-(tert-butyl)phenyl)(1Hpyrrol-2-yl)methyl)thiophen-2-yl)benzene [42] 5 were prepared by following our reported procedures and spectral data (Figure S1-S6) matched with our reported data.…”
Section: Methodsmentioning
confidence: 99%
“…The known compounds 4 a and 5 a were prepared by following our reported procedures and spectral data (Figure S4-S6) matched with our reported data. [25] The compounds 1-2 and 4 b, 5 b and 6 a-b were prepared as described below:…”
Section: Methodsmentioning
confidence: 99%
“…The crowned porphyrinoids incorporating two pyrroloindole units 44 were also synthesised ( Scheme 11 ) [ 134 ]. The electrochemical studies demonstrated low oxidation potentials, and similarly to previously described systems incorporating a single pyrroloindole unit, compound 44 underwent single-electron oxidation forming stable cation radicals.…”
Section: From Crowned Porphyrins To Crownphyrinsmentioning
confidence: 99%